2013
DOI: 10.1093/bja/aet161
|View full text |Cite
|
Sign up to set email alerts
|

An approach to neuraxial anaesthesia for the severely scoliotic spine

Abstract: We report on a case in which computed tomography was used to guide placement of an epidural catheter in a patient with severe scoliosis and congenital dwarfism. In addition, the computed tomograms were corroborated with ultrasound and fluoroscopic images in the patient. Three years later, the patient had a spinal anaesthetic performed with only the use of ultrasound-guidance. Ease of placement of the epidural and spinal was greatly enhanced by imaging. We present an algorithmic approach to neuraxial anaesthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…It is increasingly being used to guide needle insertions in the spinal region such as central neuraxial and paravertebral blocks, 1-3 particularly in patients with complex anatomies. 4,5 In a recent review by Kirkham and Chin,6 the use of ultrasound is said to reduce the number of needle insertions and redirections, minimize the risk of traumatic needle placements, and improve block effectiveness after epidural placement. However, interpreting ultrasound images and maintaining visibility of the needle tip can be challenging, particularly for trainees.…”
mentioning
confidence: 99%
“…It is increasingly being used to guide needle insertions in the spinal region such as central neuraxial and paravertebral blocks, 1-3 particularly in patients with complex anatomies. 4,5 In a recent review by Kirkham and Chin,6 the use of ultrasound is said to reduce the number of needle insertions and redirections, minimize the risk of traumatic needle placements, and improve block effectiveness after epidural placement. However, interpreting ultrasound images and maintaining visibility of the needle tip can be challenging, particularly for trainees.…”
mentioning
confidence: 99%
“…Investigators have suggested techniques like use of high-tech imaging modalities to assess the depth and intervertebral space identification to guide the needle angulation for a successful lumbar puncture. [ 10 ] In our study, with the use of simple instrument (Goniometer), we found that an acute angulation of 4° ± 2.45° for Cobb angle <50° and 9.14° ± 2.45° for Cobb angle >50° was noted for successful SAB. This was easier and the best way to approximate needle angle for successful SAB based on severity of scoliotic curve.…”
Section: Discussionmentioning
confidence: 63%
“…In cases where the spinous processes are palpable and a median approach is planned the needle should be forwarded in the transverse plane towards the convex side. The authors recommend ultrasound guided access of the subarachnoid space or an alternate modality of pain management for a severely scoliotic spine (cobb's angle >50 degrees) [15] .…”
Section: Discussionmentioning
confidence: 99%